Biological screening of a unique drug library targeting MRGPRX2 - Yang, Fan; Limjunyawong, Nathachit; Peng, Qi; Schroeder, John T.; Saini, Sarbjit; MacGlashan, Donald; Dong, Xinzhong; Gao, Li (Frontiers in Immunology, 2022)
Background: Allergic drug reaction or drug allergy is an immunologically mediated drug hypersensitivity reaction (DHR). G-protein coupled receptors (GPCRs) are common drug targets and communicate extracellular signals that initiate cellular responses. Recent evidence shows that GPCR MRGPRX2 is of major importance in IgE-independent pseudo-allergic DHRs based on the suspected interactions between many FDA-approved peptidergic compounds and MRGPRX2. Objective: Our aim was to uncover novel MRGPRX2-selective and -potent agonists as drug candidates responsible for clinical features of pseudo-allergic DHRs. Methods: We conducted a primary high-throughput screening (HTS), coupled with mutagenesis targeting the MRGPRX2 N62S mutation, on a panel of 3,456 library compounds. We discovered pharmacologically active hit compounds as agonists of the MRGPRX2 protein according to high degrees of potency evaluated by the calcium response and validated by the degranulation assay. Using the molecular tool Forge, we also characterized the structure-activity relationship shared by identified hit compounds. Results: The alternative allele of single nucleotide polymorphism rs10833049 (N62S) in MRGPRX2 demonstrated loss-of-function property in response to substance P and antineoplastic agent daunorubicin hydrochloride. We applied a unique assay system targeting the N62S mutation to the HTS and identified 84 MRGPRX2-selective active hit compounds representing diverse classes according to primary drug indications. The top five highly represented groups included fluoroquinolone and non-fluoroquinolone antibiotics; antidepressive/antipsychotic; antihistaminic and antineoplastic agents. We classified hit compounds into 14 clusters representing a variety of chemical and drug classes beyond those reported, such as opioids, neuromuscular blocking agents, and fluoroquinolones. We further demonstrated MRGPRX2-dependent degranulation in the human mast cell line LAD2 cells induced by three novel agonists representing the non-fluoroquinolone antibiotics (bacitracin A), anti-allergic agents (brompheniramine maleate) and tyrosine-kinase inhibitors (imatinib mesylate). Conclusion: Our findings could facilitate the development of interventions for personalized prevention and treatment of DHRs, as well as future pharmacogenetic investigations of MRGPRX2 in relevant disease cohorts.